Aplikasi Pembelajaran Mudah Alih Sejarah Menggunakan Pendekatan Pembelajaran Berasaskan Permainan - Roosli, Fauzon Nur Yusliza; Ismail, Mohd Norasi (Applied Information Technology And Computer Science, 2025)
A mobile learning application themed about History for topic 9 and topic 10 by using Game-Based Learning techniques was selected as a research domain to overcome the problems of students who have difficulty scoring in the subject of History. The purpose of this project is to design a Malaysian History application using a game-based learning technique approach and the game is a 2D side scrolling game. Also, the purpose of this project is to test the functionality and usability of the developed application and user acceptance. The methodology used is the Game Development Life Cycle (GDLC) which has 6 phases. The result of this project is an application developed that can overcome the problem and can work well. Testing against target users had been done. The result of the test has got a score of 91.91 where user accept the application.